Review: The Edinburgh Companion to Virginia Woolf and Contemporary Global Literature. By Jeanne Dubino, Paulina Pająk, Catherine W. Hollis, Celiese Lypka & Vara Neverow (eds.), Edinburgh University Press, 2020. Pp. 465. - Buchowska, Dominika (Studia Anglica Posnaniensia, 2021)
Review: The Edinburgh Companion to Virginia Woolf and Contemporary Global Literature. By Jeanne Dubino, Paulina Pająk, Catherine W. Hollis, Celiese Lypka & Vara Neverow (eds.), Edinburgh University Press, 2020. Pp. 465.